Вплив тенденцій глобалізації на умови забезпечення антикризової стратегії в процесі реалізації державної економічної політики - Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna (My University, 2015)
UK: Здійснено аналіз впливу тенденцій глобалізації на умови забезпечення антикризової стратегії в процесі реалізації державної економічної політики. Встановлено, що розвиток глобальних тенденцій актуалізує проблему антикризового регулювання у контексті забезпечення економічної безпеки країни з боку зовнішніх впливів. Доведено необхідність формування нового підходу до антикризового регулювання в умовах глобалізації. EN: The analysis of the impact of globalization trends in the condition of the anti-crisis strategy. It was established that the development of global trends actualizes the problem of crisis management in the context of economic security from external influences as reproductive process can no longer be effectively implemented in the national framework. It only seems consistent with the growing globalization of the relationship on a planetary scale. Existing differences in economic potential and national interests, the desire for better isolating them from the global interests of large counterweight act of integration trends. Proved that all conflicts of interest implemented by individual countries in the global economic space increasingly evident necessity of forming a new approach to crisis management in the context of globalization, able to ensure the stability conditions for the functioning and development of the national economies of the world and uniting their efforts the fight against global financial crisis and other global challenges. Development and implementation of this approach requires adjustments of international relations on the concept of balance of power on the concept of balance of national interests, moving from confrontational ideology of economic security type for models based on partnerships and international economic cooperation.
Influence of globalization trends in terms of support anti-crisis strategy in the process of the realization of the state economical policy
Keywords: антикризова стратегія; галузі економіки; глобалізація; держава; економічна політика; реальний сектор економіки; anti-crisis strategy; economics; globalization; the state; economical policy; the real economy